Cybersecurity issues, challenges, and solutions in the business world - Verma, Suhasini; Vyas, Vidhisha 1980-; Kaushik, Keshav (Information Science Reference, an imprint of IGI Global, 2023)
"This book centers on the basics of cybersecurity innovation alongside the methods and strategies for organizations to adopt, allowing readers to have a more profound comprehension of cybersecurity in the business world"--
Keywords: Data protection / Economic aspects; Database security / Economic aspects; Computer security / Economic aspects; Electronic books